2020
DOI: 10.1038/s41375-020-01095-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-10a as a therapeutic target and predictive biomarker for MDM2 inhibition in acute myeloid leukemia

Abstract: Pharmacological inhibition of MDM2/4, which activates the critical tumor suppressor p53, has been gaining increasing interest as a strategy for the treatment of acute myeloid leukemia (AML). While clinical trials of MDM2 inhibitors have shown promise, responses have been confined to largely molecularly undefined patients, indicating that new biomarkers and optimized treatment strategies are needed. We previously reported that the microRNA miR-10a is strongly overexpressed in some AML, and demonstrate here that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Comparison between our work and a salivary biomarker study in the literature for AUD ( Rosato et al, 2019 ) found hsa-miR-10a-5p and miR-27a-5p as significantly upregulated in both studies. Alterations in miR-10a expression have been important in multiple types of cancers, likely through its role in the regulation of p53 ( Ovcharenko et al, 2011 ; Bryant et al, 2012 ; Vu et al, 2021 ), a highly conserved, critical tumor suppressor gene. As a result, miR-10a has proven to be an important cancer biomarker ( Vu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between our work and a salivary biomarker study in the literature for AUD ( Rosato et al, 2019 ) found hsa-miR-10a-5p and miR-27a-5p as significantly upregulated in both studies. Alterations in miR-10a expression have been important in multiple types of cancers, likely through its role in the regulation of p53 ( Ovcharenko et al, 2011 ; Bryant et al, 2012 ; Vu et al, 2021 ), a highly conserved, critical tumor suppressor gene. As a result, miR-10a has proven to be an important cancer biomarker ( Vu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because many microRNAs are differentially expressed in pathological cells compared to normal cells, attempts are being made to use microRNAs as biomarkers in several diseases, e.g ., in neurological disorders ( Shafi et al, 2010 ; Wang et al, 2021 ) cancer ( Vu et al, 2021 ), infections ( Wang et al, 2016 ), aging ( Kumar et al, 2017 ) and forensics ( Silva et al, 2015 ). Interestingly, microRNAs emerge as attractive biomarkers of cancer as microRNA profiling seems to more accurately cluster different types of cancer rather than mRNA ( Lu et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…MDM4 knockdown activated p53, induced cell-cycle arrest, and lowered the growth of tumor in a xenograft model (Hullein et al, 2019). Recently, pharmaceutical inhibitors targeting MDM2 and MDM4 have been explored to reactive the p53/Rb tumor suppressor function; and the preliminary response data from the clinical trial in acute myeloid leukemia patients have been gaining increasing interest (Burgess et al, 2016;Vu et al, 2020). Likewise, our findings give an insight into the DOX-PMs-NPMBP-induced MDM2 and MDM4 dual inhibition, which might put forward the clinical perspectives of DOX-PMs-NPMBP to ALL therapy.…”
Section: Discussionmentioning
confidence: 62%
“…All NPM1 mutant/FLT3-ITD wild cases were from the low HOTAIR expression group (p = 0.017), and 40% of the double NPM1/FLT3-ITD mutant cases were from the low expression group. Since all NPM1 mutations increased cytoplasmic concentrations of NPM1 protein, NPM1 modulates stress response and growth suppression by binding to and stabilizing p53 and inhibiting MDM2 [29].…”
Section: Discussionmentioning
confidence: 99%